Social status and leadership: The case of the school executive - Seeman, Melvin (Columbus, 1960)
Early in their discussion of leadership, the authors of The Ameri- can Soldier commented on the urgent need for "some tested hypothe- ses to replace the copybook maxims that now fill most manuals on leadership" (74, page 363).' The present volume, focusing on the schools as an arena for leadership, is intended as one contribution to a growing literature of the kind they envisioned. I have tried to apply a careful, empirical attitude to operating organizations and to test, with these ongoing institutions, a relatively systematic set of propositions about leadership in America. Such a procedure has obvious limitations in regard to control of relevant variables, limita- tions which this study does not escape.
Keywords: Sociology